Low-dose ketoconazole-fluconazole combination versus fluconazole in single doses for the treatment of vaginal candidiasis (Faculty of Medicine Universitas Indonesia, 2011)
Background: Vaginal candidiasis (VC) is one of the most common fungal diseases. Candida albicans is the most common causative fungus and has been isolated from more than 80% of specimens obtained from women with VC. Ketoconazole is the first orally active antifungal, the dosage for VC is 200 mg twice daily for 5 days. Fluconazole is the newer oral antifungal, its dosage for VC is a single oral dose of 150 mg. Since fluconazole 150 mg is considerably expensive, a single dose of 100 mg ketoconazole and 40 mg fluconazole in combination has been tested for the treatment of VC. The results showed that from 11 women with confirmed VC, 1-2 weeks after drug administration, the mycological culture was negative in 8 women, positive in 1 woman, and 2 woman lost to follow-up. This promising result led to the present study with the objective to confirm the efficacy and safety of the above combination in a formal clinical trial. Methods: A total of 165 female patients, aged 18 years or older, with the diagnosis of VC from clinical symptoms (pruritus or burning or excessive discharge) and positive microscopic smear (pseudohyphae and/or yeast cells) were randomized to receive a single dose of either keto-fluco combination (n = 85) or fluconazole (n = 80), and returnedfor follow-up visit on day 8. Results: Among these patients, 39 patients had negative baseline culture, leaving 126 patients eligible for efficacy evaluation. The mycological eradication in the keto-fluco group was 74.5% (41 patients from a total of 55 patients with available mycological culture), while that in the fluconazole group was 70.2% (40 patients from 57 patients with available culture) and this difference was not significant. The clinical favorable response (clinical cure and clinical improvement) in the keto-fluco arm (n = 60) was 98.3%, while that in the fluconazole group (n = 66) was 100%. Adverse events were found in 5 patients, 3 patients in the keto-fluco group (3/85 = 3.5%) and 2 patients in the fluconazole group (2/80 = 2.5%). Conclusion: The present study showed that the efficacy and safety of ketoconazole 100 mg and fluconazole 40 mg combination was not inferior compared to fluconazole 150 mg in single doses for the treatment of vaginal candidiasis. (Med J Indones 2011; 20:205-11)